Parasites Of Scavenging Chickens In Penang Island - Meor Termizi, Farah Haziqah (2011)
Scavenging chicken or ‘ayam kampung’ is of a dual-purpose type, reared for both its meat and eggs. ‘Ayam kampung’ meat is preferred by most consumers, probably due to its specific texture and taste. Most of the rural villagers raise the chickens in small flocks for subsistence, hobby or simply for pleasure. The chickens are left scavenging around the backyards and feed mainly on kitchen wastes, worms, snails, insects and vegetation. Thus, the parasitic infection is commonly high due to an increase opportunity to encounter the infective eggs, larvae, and intermediate hosts of parasites. The aims of this study were to examine the state of nutrition or body condition and the presence of internal and external parasites of 240 scavenging chickens (Gallus domesticus) obtained randomly from 12 divisions (Mukim) in Penang Island.